Respuesta :

Answer:

see explanation

Step-by-step explanation:

(1)

y = - x + 4 ( add x to both sides )

x + y = 4

with A = 1, B = 1, C = 4

(2)

y = 5x + 7 ( subtract y from both sides )

0 = 5x - y + 7 ( subtract 7 from both sides )

- 7 = 5x - y , that is

5x - y = - 7

with A = 5, B = - 1, C = - 7

----------------------------------------------------------

(1)

2x + y = 9 ( subtract 2x from both sides )

y = - 2x + 9

with m = - 2, c = 9

(2)

5x + 2y = 7 ( subtract 5x from both sides )

2y = - 5x + 7 ( divide terms by 2 )

y = - [tex]\frac{5}{2}[/tex] x + [tex]\frac{7}{2}[/tex]

with m = - [tex]\frac{5}{2}[/tex] , c = [tex]\frac{7}{2}[/tex]